2020
DOI: 10.1002/adsc.202000483
|View full text |Cite
|
Sign up to set email alerts
|

Monosubstituted, Anionic Imidazolyl Ligands from N−H NHC Precursors and Their Activity in Pd‐Catalyzed Cross‐Coupling Reactions

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…For example, when ligand 1 was mixed with PdCl 2 in methanol, only a monomeric Pd complex 2 was obtained, where Pd was inserted between the P–C bond of the ligand (Figure a). We recently demonstrated that this new N–H N-heterocyclic carbene–palladium complex is highly active in palladium-catalyzed Suzuki–Miyaura reactions . In contrast, we found that if ligand 1 was first coordinated with a boron Lewis acid to form 3 , formation of a bimetallic Pd­(II) complex 4 was observed upon addition of PdCl 2 in dioxane (Figure b).…”
Section: Results and Discussionmentioning
confidence: 87%
“…For example, when ligand 1 was mixed with PdCl 2 in methanol, only a monomeric Pd complex 2 was obtained, where Pd was inserted between the P–C bond of the ligand (Figure a). We recently demonstrated that this new N–H N-heterocyclic carbene–palladium complex is highly active in palladium-catalyzed Suzuki–Miyaura reactions . In contrast, we found that if ligand 1 was first coordinated with a boron Lewis acid to form 3 , formation of a bimetallic Pd­(II) complex 4 was observed upon addition of PdCl 2 in dioxane (Figure b).…”
Section: Results and Discussionmentioning
confidence: 87%
“…Tolman electronic parameter comparisons between this ligand and other common NHC ligands showed that the anionic imidazolyl ligand of 2a was significantly more donating in Suzuki–Miyaura cross-couplings. The v CO value was shifted by >40 cm –1 for DFT-calculated Ni­(CO) 3 (NHC) structures . Unfortunately, diarylphosphine complexes like 2a had very low reactivity toward cross-couplings with aryl chloride substrates.…”
mentioning
confidence: 59%
“…The absence of methanol in the reactions leads to no product formation with 5b (entry 5) and 39% conversion with the mixture of 2c + 5c (entry 6). Previously we have found that methanol is essential for formation of the N–H NHC complex to occur, which suggests that the N–H NHC form of the t -butyl catalyst ( 2b ) may actually be present in the reaction. The fact that the mixture of 2c + 5c does give some product in the absence of methanol further supports our hypothesis that the N–H NHC form of the catalyst is important for efficient catalysis.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…For the Buchwald–Hartwig reaction, we see only a slight shift in the 31 P NMR spectra for complex 1 and a small amount of free ligand (3.5:1 ratio of 1 to free ligand). The phosphorus shift for complex 1 is likely the result of chloride exchange . In addition, the mass spectrum (MS) of the crude reaction mixture shows mainly dimeric palladium species, suggesting that catalyst breakdown to a monometallic species is not particularly preferred.…”
mentioning
confidence: 99%